Analysis of The use of Proteus Software as a Practical Learning Support - Arif, Arif Rakhman Suharso; Akhmad Nuriyanis; Ario Hendartono; Evi Sirait; Fajar Sari Kurniawan; Candra Oktyasari Putri (Nusa Putra University, 2024)
This research aims to increase understanding of electronics and control systems practicum using Proteus software and practicum directly using electronic components. Proteus software is used to complement the limited equipment in the electrical laboratory and control laboratory. Data was collected using the success rate of cadets in increasing their practical understanding of electronics and control systems courses using Proteus software to complete the practicum using electronic components and simulators in learning from 16 meetings and added with UTS and UAS. The use of Proteus software for practical activities is based on the need to improve cadet skills which is based on the fact that around 76% of cadets who take part in electronics and control systems practicum do not understand electronic circuits because the practicum only uses a simulator board so it needs to be combined with Proteus software to better understand the material involved. given. Apart from the limitations of electronic component equipment, Proteus software is used. The results showed that using Proteus software, 97% of cadets were able to take part in this learning, which had a positive impact on learning outcomes and cadet activities.